Blood loss after coronary artery bypass by aspirin responsiveness assessed with preoperative VerifyNow aspirin testing. Issue 8 (27th December 2021) - Willemsen, Laura M.; Vlot, Eline A.; Janssen, Paul W. A.; Visser, Claire D.; Zheng, Kai; Kelder, Johannes C.; Noordzij, Peter G.; van den Dool, Erik‐Jan; Klein, Patrick; Hackeng, Christian M.; ten Berg, Jurrien M.
Abstract: Background: Aspirin is important for preventing thrombotic events but also increases bleeding complications. Minimizing bleeding while preventing thrombotic events remains challenging in patients undergoing coronary artery bypass grafting (CABG). Establishing the patient's preoperative aspirin response could distinguish patients at risk for perioperative blood loss. Objective: Aim was to compare 12‐h blood loss after CABG between aspirin‐sensitive and aspirin‐resistant patients. Patients/Methods: The primary analysis of this substudy of the POPular CABG trial (NCT02352402) included patients that used aspirin monotherapy preoperatively. A preoperative platelet function test by the VerifyNow aspirin assay was performed before CABG and patients were classified as aspirin‐sensitive or aspirin‐resistant based on an aspirin reaction units cutoff value of 550. The primary end point was 12‐hour blood loss after CABG. The secondary end point was, among others, clinical bleeding events after CABG. Results: A total of 128 patients were included in the primary analysis. Of these, 116 patients were aspirin sensitive and 12 were aspirin resistant. Mean blood loss 12 hours after CABG was 555 ± 278 mL in aspirin‐sensitive patients and 406±110 mL in aspirin‐resistant patients ( P = .04). All bleeding events (n = 15; 11.7%) occurred in aspirin‐sensitive patients. Conclusions: In patients who are on aspirin preoperatively, aspirin sensitivity was associated with 12‐hour blood loss after CABG, suggesting that preoperative VerifyNow aspirin testing could identify patients undergoing CABG at high risk for perioperative bleeding.